2015
DOI: 10.1016/j.celrep.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Activators of the NLRP3 Inflammasome Promote IL-1β Secretion by Triggering Necrosis

Abstract: The NLRP3 inflammasome is involved in caspase-1-dependent maturation of IL-1β in many contexts. A two-signal model has emerged for IL-1β maturation, with LPS providing "signal I" and diverse agents such as ATP, Nigericin, streptolysin O, uric acid crystals, and alum salts capable of acting as "signal II." In the absence of signal II, pro-IL-1β is upregulated but typically fails to be processed or released. What unites signal II stimuli has been debated, with the ability to promote K+ efflux suggested as a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
165
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(188 citation statements)
references
References 36 publications
18
165
3
Order By: Relevance
“…As such, we could not conclusively determine if IL-1β secretion was an active or passive process during necroptosis. This question of whether IL-1β can be actively secreted from cells after caspase-1 activation remains controversial (20,23,(35)(36)(37). These experiments nonetheless suggested that NLRP3 activation could be cell-intrinsic, because glycine treatment had no effect on mature IL-1β secretion following MLKL activation.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we could not conclusively determine if IL-1β secretion was an active or passive process during necroptosis. This question of whether IL-1β can be actively secreted from cells after caspase-1 activation remains controversial (20,23,(35)(36)(37). These experiments nonetheless suggested that NLRP3 activation could be cell-intrinsic, because glycine treatment had no effect on mature IL-1β secretion following MLKL activation.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α can activate pro-apoptotic pathways 27 and production and release of mature Il-1β may occur when the permeability of the cell membrane is increased, potentially triggering cell necrosis 28 . To determine if bactericidal antibiotic treatment is also associated with cell death, we measured excretion of LDH by SNECs - LDH is released by dying mammalian cells and has been used as a marker of cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their roles in inflammation, both TNF-α and IL-1β are also associated with activation of pro-apoptotic or necrosis death pathways 27,28 . In this study, we also demonstrate that treatment with levofloxacin and amoxicillin for 48 and 96-hours is cytotoxic (as measured by LDH secretion) to human SNECs compared to untreated SNECs (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…[50][51] It was shown that only when cell membrane disruption and necrotic cell death was initiated by wellknown activators of the NLRP3 inflammasome, IL-1β could be released from the cytosol. 54 Corroborating this finding and underpinning the importance of plasma membrane rupture, cleavage of gasdermin D by both caspase-1 and caspase-4/-5/-11 appeared crucial for the execution of pyroptosis and the release of mature IL-1β. [55][56][57] An alternative (or integrated) pathway of execution of pyroptosis could be the caspase-11-dependent cleavage of pannexin-1, which leads to ATP release and subsequent purinergic P2X7-receptor-mediated plasma membrane permeabilization.…”
Section: Pyroptosis: Inflammatory Cell Deathmentioning
confidence: 92%